2016
DOI: 10.3402/gha.v9.29575
|View full text |Cite
|
Sign up to set email alerts
|

Early sexual initiation and multiple sexual partners among Vietnamese women: analysis from the Multiple Indicator Cluster Survey, 2011

Abstract: IntroductionUnder current HIV transmission mechanisms operating in Vietnam, women are seen as victims of their male partners. Having multiple sexual partners is one of the well-known risk factors for HIV infection. However, little is known about women's risky sexual behaviour and their vulnerability to HIV in Vietnam. This study aims to explore association between early sexual initiation and the number of lifetime sexual partners in Vietnamese women. Although the Vietnamese culture is socially conservative in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
4
24
0
2
Order By: Relevance
“…Our finding on the association between age at sexual debut and having multiple sexual partners among women is in line with several previously published studies. Multiple Indicator Cluster Survey study on Vietnam found significant association between early sexual debut with having lifetime multiple sexual partners ( 31 ). The same study also reported that first sexual intercourse before 19 years increased the likelihood of having multiple sexual partners by a factor of five.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding on the association between age at sexual debut and having multiple sexual partners among women is in line with several previously published studies. Multiple Indicator Cluster Survey study on Vietnam found significant association between early sexual debut with having lifetime multiple sexual partners ( 31 ). The same study also reported that first sexual intercourse before 19 years increased the likelihood of having multiple sexual partners by a factor of five.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, it was not possible to include variables from all these domains, as subjective well-being was not the main focus of the survey. Based on the availability of the variables on the dataset, the following were included in the analysis: Age (15)(16)(17)(18)(19)(20)(21)(22)(23)(24); sex (Male/Female); marital status (Currently Married/Formerly Married/Never Married); region (Northern/Central/Southern); satisfaction with living condition (Not satisfied/Satisfied); religion (Islam and other/Christian); wealth quintile ((Poorest or Q1)/Second or Q2/Middle or Q3/Fourth or Q4/Richest or Q5)); ethnicity (Chewa/Tumbuka/Lomwe/Yao/Ngoni/Other); education (None/Primary/Secondary); has children (Yes/No); ever smoke (Yes/No); ever drink (Yes/No); media use (Yes/No) (Ngamaba and Soni 2018;Bishwajit et al 2017;DeSalvo et al 2006;Balogun et al 2017;Chin 2010;Cheung and Lucas 2014;He et al 2018;Son et al 2016;Ghose 2017).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…The index is constructed by principal components analysis of scores assigned on individual household possessions, e.g., consumer goods, dwelling characteristics. Households are then ranked based on individual scores to range between poorest, poorer, middle, richer, and richest (Son et al 2016). Media use was measured by self-reported use of TV and radio.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Por otro lado Son, en adolescentes vietnamitas, informa que solo el 5 % de las mujeres utilizaron preservativo durante la primera relación sexual (17). Este hecho se explicaría, en parte, en que la prioridad de las adolescentes es la prevención del embarazo o evitar el enojo de sus parejas, por lo que prefieren el uso de métodos hormonales por sobre otros, y no consideran el riesgo de exposición a ITS (18).…”
Section: Discussionunclassified